Lidar-led fieldwork in the Eretria-Amarynthos Survey Project (Euboea, Greece) - Fachard, Sylvian; Chezeaux, Chloé; Castiello, Maria Elena (Journal of Greek Archaeology, 2025)
This paper provides a brief overview of lidar research developed in the framework of the Eretria-Amarynthos Survey Project (EASP). Over the course of four field seasons, the implementation of lidar-based remote sensing and ground-truthing has become an integral part of the examination of archaeological landscapes, resulting in significant advances in fieldwork practices, survey methodology, and data recording. We argue here that lidar holds great potential for archaeological survey in Greece, particularly in rugged and sloped terrain, which represents up to 80% of landforms in Central Greece, thus opening new ways of inquiry and dramatically increasing archaeological survey potential outside of agricultural and flat terrain.